Patent Protection for Computer Programs in India: Need for a Coherent Approach - Pai, Yogesh Anand (The Journal of world intellectual property, 2007)
The 2002 amendment to the Indian Patents Act, 1970, allowed computer program‐related inventions to be patentable, save for certain specific exclusions. The Patent (Amendment) Ordinance of 2004 tried to expand the scope of computer program patentability by melting down those specific exclusions. In 2005, the Indian Parliament categorically rejected the amendments as suggested in the Ordinance, thereby maintaining the status quo on the issue. The new legislative context advocated that a proper interpretation fostering the Parliament's intention be undertaken. Interestingly, the persistent policy of the Indian Patent Office is in favor of expanding notions of computer program patentability, as reflected in its draft manuals, suggesting interpretations quite contrary to the legislative intention and the statutory mandate. The need recommends that the Indian Patent Office does not fall in line with its US and EU counterparts, which are now being accused of granting “questionable patents”, thereby taciturnly mooting for a serious patent law reform. The current taste of disapproval for intrinsic patentability of computer programs is corroborative of the original interpretations suggested here, as connoting the exact intention of the Indian Parliament.